Predicting Attitudes towards Protected Area Management in a Developing Country Context - Mwesigye Tumusiime, David; Byakagaba, Patrick; Tweheyo, Mnason; Turyahabwe, Nelson (Journal of Sustainable Development, 2018)
Biodiversity conservation through use of protected areas relies significantly on the attitudes of local adjacent communities. Some studies suggest that attitudes are often shaped by the associated positive and negative externalities and socio-demographic and economic characteristics of local communities living adjacent to protected areas. The current study sought to identify useful predictors of local attitudes towards protected area management. It was conducted at Bwindi Impenetrable National Park in Uganda where several interventions in form of benefits to improve local people’s attitudes towards the park have been implemented for the last 30 years. The study examined the extent to which these benefits can influence local people’s attitude towards management of the Protected Area (PA). A household survey was conducted among 190 randomly selected respondents and Generalised Linear Mixed Models (GLMMs) fitted where the dependent variable was a binary “Good” or “otherwise” response to how the respondent considered own relationship with park management. Socio-economic attributes of the respondents were used as control variables. The importance of cost variables (e.g. crop raiding) was also examined. The study found that only direct and material benefits were consistent predictors of a positive attitude towards management. Non-material and indirect benefits as well as the socio-economic factors and costs did not influence the attitude of local communities towards management. It can be concluded that positive attitude towards protected area management is determined by access to direct and material benefits by local communities and not socio-economic factors or costs incurred. Interventions intended to influence local communities to have a positive attitude towards management ought to emphasize direct and material benefits.
Keywords: Bwindi; Protected area benefit sharing; Tourism revenue